Paying fees for using retail permits alcoholic beverages intended for consumption at the point of sale during the epidemic (Discourse of Law and Administration, 2022)
During the SARS-Cov2 epidemic, many entrepreneurs engaged in catering activities, including those engaged in the sale of alcohol under their permits, were unable to use these permits. This study aims to answer the question: are entrepreneurs who, in fact, in relatively long periods of time ‒ in which the legislator himself has excluded the possibility of running a business ‒ have not used the permits to sell alcohol, are obliged to pay the above-mentioned fees. And if the answer to the above question is negative, then how can they apply for the reimbursement of previously paid fees for the periods in which they were deprived of the possibility of using the permits for the sale of alcoholic beverages under the so-called “Gastronomy”. Moreover, are municipal councils authorized to exempt entrepreneurs from these fees and what is the scope of their powers in this regard.
Keywords: fees for the use of permits for the sale of alcohol; the anti-alcohol act; special legal solutions during the epidemic